Comprehensive Open Management of Buttock/Ischiofemoral Symptoms: The COMBIS Procedure for Posterior Hip Pain - Andrew J. Curley MD; Joshua C. Setliff BA; Justin J. Greiner MD; Laura E. Keeling MD; Craig S. Mauro MD (SAGE Publishing, 2022)
Background: Posterior hip and buttock pain can arise from several overlapping but distinct etiologies. Ischiofemoral impingement, sciatic neuropathy, and proximal hamstring tendinopathy, occurring alone or in combination, have been implicated as precipitants. However, diagnosis and management of underlying pathology can be challenging, as few diagnostic modalities reliably differentiate between these etiologies and surgeon decision-making may be complicated by uncertainty over which pathology to address. Indications: Posterior hip and buttock pain which occurs in a sciatic nerve distribution and is refractory to conservative measures (eg, physical therapy, analgesics, and activity modification) raises suspicion for 1 or several of the above pathologies. A combined procedure to address all 3-ischiofemoral decompression, sciatic neurolysis, and proximal hamstring repair-is described here. Technique Description: The patient is placed prone on a radiolucent table. An incision is made, and dissection is taken down through the superficial layers of the buttock, gluteal fascia, and fascia overlying the proximal hamstring tendons. The sciatic nerve is identified, mobilized, and lysed using blunt dissection. The fascia overlying the ischium is incised and the tendinous insertion decorticated with rongeur. Two anchors are placed, and sutures are passed through the proximal hamstring tendon in mattress fashion. An incision is made in line with the external rotators and dissection is taken down to the lesser trochanter. The lesser trochanter is identified, and osteotomy performed, with mobilization and removal of the resected fragment. The interval in the external rotators is closed with interrupted suture. Results: This is an uncommon procedure with little data on patient outcomes. Nonetheless, it is effective for relief of symptoms related to the pathologies enumerated above. Keys to success include careful diagnosis and comfort with surgical technique. Conclusion: The COMBIS procedure simultaneously addresses 3 common etiologies of posterior hip and buttock pain. Although it is important to conduct a thorough diagnostic evaluation to rule out imitators, patients with symptoms due to ischiofemoral impingement, sciatic neuropathy, proximal hamstring tendinopathy, or combination thereof may experience good relief of symptoms with appropriate application of this technique. The author(s) attests that consent has been obtained from any patient(s) appearing in this publication. If the individual may be identifiable, the author(s) has included a statement of release or other written form of approval from the patient(s) with this submission for publication.